Association of achondroplasia with sagittal synostosis and scaphocephaly in two patients, an underestimated condition?. (March 2015) - Accogli, Andrea; Pacetti, Mattia; Fiaschi, Pietro; Pavanello, Marco; Piatelli, Gianluca; Nuzzi, Daniele; Baldi, Maurizia; Tassano, Elisa; Severino, Maria Savina; Allegri, Anna; Capra, Valeria
<x xml:space="preserve">Abstract</x> We report on two patients with an unusual combination of achondroplasia and surgically treated sagittal synostosis and scaphocephaly. The most common achondroplasia mutation, p.Gly380Arg in fibroblast growth factor receptor 3 (FGFR3), was detected in both patients. Molecular genetic testing of FGFR1, FGFR2, FGFR3 and TWIST1 genes failed to detect any additional mutations. There are several reports of achondroplasia with associated craniosynostosis, but no other cases of scaphocephaly in children with achondroplasia have been described. Recently it has been demonstrated that FGFR3 mutations affect not only endochondral ossification but also membranous ossification, providing new explanations for the craniofacial hallmarks in achondroplasia. Our report suggests that the association of isolated scaphocephaly and other craniosynostoses with achondroplasia may be under recognized. © 2015 Wiley Periodicals, Inc.